The schizophrenia spectrum - Silverstein, Steven M.; Spaulding, William D. 1950-; Menditto, Anthony A (Advances in psychotherapy--evidence-based practice, 2016)
"The new edition of this highly acclaimed volume provides a fully updated and comprehensive account of the psychopathology, clinical assessment, and treatment of schizophrenia spectrum disorders. It emphasizes functional assessment and modern psychological treatment and rehabilitation methods, which continue to be under-used despite overwhelming evidence that they improve outcomes. The compact and easy-to-read text provides both experienced practitioners and students with an evidence-based guide incorporating the major developments of the last decade: the new diagnostic criteria of the DSM-5, introducing the schizophrenia spectrum and neurodevelopmental disorders, the further evolution of recovery as central to treatment and rehabilitation, advances in understanding the psychopathology of schizophrenia, and the proliferation of psychological and psychosocial modalities for treatment and rehabilitation."--